A PID - Ziegler Nichols Method for Load Frequency Control - Anggraini, Dessy Dwi; Palaloi, Sudirman; Maharani, Markies Diana Desy; Sularso, Adhimas Herjuno; Manurung, Rosa Tiarmin; Habibi, Rizky Maulana Iqwan; Aditya, Putra Yoga; Harsito, Catur (Faculty of Advanced Technology and Multidiscipline Universitas Airlangga, 2025)
Dynamic load variations significantly impact the stability of system frequency, necessitating the implementation of Load Frequency Control (LFC) to maintain frequency stability. In this study, a PID-based control approach is applied to LFC modeling using the Ziegler-Nichols tuning method through the Reaction Curve Method. The test was conducted using the difference of load of 1 p.u. Using these parameters, the optimal PID controller was configured with Kp = 2.97, Ki = 0.78, and Kd = 2.27. The evaluation demonstrated that the system achieved a settling time of 17 seconds and a maximum overshoot of 65.35 Hz. Under various load scenarios, including increasing, decreasing, and fluctuating loads, the LFC system equipped with a PID controller based on the Ziegler-Nichols Reaction Curve Method effectively maintained frequency stability despite significant load changes. These findings confirm that the proposed approach is reliable in preserving system performance under dynamic load conditions.